A21 Role 1–4 care in Ukraine to prevent multidrug-resistant organism infections in large-scale combat operations: a biological warfare-inspired protocol for combat casualty care in Ukraine - Hailie Uren; B Hudson Berrey; Kostiantyn Gumeniuk; Volodymyr Kovalchuk; Olena Moshynets; Uliana Pidvalna; Dmytro Beshley; Mykola Ankin; Yvette Godwin; Douglas Davis; John Holcomb (BMJ Military Health, 2025)
Background In modern warfare, surviving the battlefield no longer guarantees survival. In Ukraine, the transition from frontline injury to definitive care now carries a heightened risk of infection with multidrug-resistant organisms (MDROs). 1–3 These infections are not isolated events; they are now driving sepsis, secondary amputations, and preventable deaths within Ukraine’s trauma system. Clinicians across the UK and Europe are reporting Ukraine derived MDROs. 4–7 We propose that rapid early (Level 1 and 2) decontamination of both the casualty and environment to be a more efficient and impactful approach compared with the late, resource-demanding pharmacological treatment of infection with MDROs. The crisis environment of a conflict requires interventions as early as possible within the evacuation pathway to prevent such infections. Objectives This study aims to strengthen Infection Prevention and Control (IPC) practices in Role 1–4 military settings in Ukraine by updating Clinical Practice Guidelines (CPGs). 8–9 Methods Structured interviews were conducted with key Ukrainian Ministry of Defence and Ministry of Health stakeholders and a US Department of Defense workshop to identify operational gaps, contextual barriers and system enablers. These findings informed the development of a revised IPC CPG, incorporating evidence-based, layered and scalable interventions adapted to the realities of conflict-affected trauma care. The next phase will implement the guideline in selected Role 1–4 settings using mixed methods, including IPC practice audits, microbiological surveillance, and qualitative staff feedback to assess feasibility, adherence, and early clinical impact at selected Roles 1–4. Results Our findings support a Multidisciplinary (MDT) layered approach at all levels of care. At all Roles 1–4, strict hand hygiene, person protective equipment (PPE), and environmental disinfection of facilities and evacuation platforms are mandated. The focus of the new guidance is on prevention of later infection by mitigating contamination and colonisation, through early and frequent decontamination via standardized antiseptic protocols. The new CPG will address: Role 1: Frontline care Potable water wound irrigation and antiseptic included in Individual Load Carrying Equipment (ILCE). Wounds should be irrigated immediately, antiseptic applied, sterile gauze placed, and early gram-positive coverage (cefazolin) given. Role 2: Forward surgical care Immediate full-body antiseptic decontamination of casualties upon arrival. Wounds irrigated with high-volume low-pressure potable water, followed by Dakins or alternative topical antiseptic prior to further movement. Early IV/PO cefazolin is reinforced. Role 3: Comprehensive hospital care Daily whole-body cleansing (at minimum pre-admission full-body antiseptic decontamination), systematic review/replacement of invasive devices, and operative debridement at least every 48h. Topical antiseptic is recommended when Negative Pressure Wound Therapy (NPWT) is not available. At this level, patients with systemic infection require broadened antibiotic coverage, recognizing frequent under-dosing and incomplete regimens. Role 4: Definitive care Emphasis on early wound closure when feasible, culture-guided systemic antibiotics, and daily antiseptic cleansing. Continuity of decontamination and wound care reduces MDRO transmission carried through the evacuation chain. Conclusions In the Russian-Ukrainian war, MDROs are now a key driver of preventable morbidity and mortality among war-wounded patients. The new CPG provides a benchmark framework for infection prevention in prolonged evacuation and highly contaminated conflict environments, and is relevant for the large scale combat operation reality. Disclosures Hailie Uren: Aspen Medical - partially funded salary. Advisory Board member for Global Medical Knowledge Alliance (GMKA), Adjunct Lecturer for Griffith University. John B Holcomb: JBH reports grants or contracts to their institution from the Defense Advanced Research Projects Agency, the US Department of Defense, the National Institutes of Health, and Commonwealth Serum Laboratories. They have received payment or honoraria from Aspen Medical, Infrascan, Geneva Foundation, and Wake Forest Institute for Regenerative Medicine, as well as support for travel or meeting attendance from several academic institutions and medical conferences. JBH holds board positions with Hemostatics, Zibrio, and the Prehospital Blood Transfusion Coalition Initiative, serves on a data and safety monitoring board for a DoD-funded project, holds stock or stock options in multiple medical companies, and is a coinventor of patents and a medical device, for which they receive royalties. The other co-authors have no conflicts of interest. References Uren HD, Aliieva N, Matolinets N, et al . Conflict zone medical evacuations catalyzing antimicrobial resistance spread and threatening regional health: a retrospective comparative observational study. J Trauma Acute Care Surg. 2025; 99 (3S). doi: 10.1097/TA.0000000000004729 Pallett SJC, Boyd SE, O’Shea MK, et al . The contribution of human conflict to the development of antimicrobial resistance. Commun Med. 2023; 3 (1):153. doi: 10.1038/s43856–023-00386–7 Kovalchuk V, Kondratiuk V, McGann P, et al . Temporal evolution of bacterial species and their antimicrobial resistance characteristics in wound infections of war-related injuries in Ukraine from 2014 to 2023 . J Hosp Infect . 2024; 15 2:99–104. doi: 10.1016/j.jhin.2024.06.011 Sandfort M, Hans JB, Fischer MA, et al . Increase in NDM-1 and NDM-1/OXA-48-producing Klebsiella pneumoniae in Germany associated with the war in Ukraine, 2022. Euro Surveill . 2022; 27 (50). doi: 10.2807/1560–7917.ES.2022.27.50.2200926 Zwittink RD, Wielders CC, Notermans DW, et al . Multidrug-resistant organisms in patients from Ukraine in the Netherlands, March to August 2022. Euro Surveill. 2022; 27 (50). doi: 10.2807/1560–7917.ES.2022.27.50.2200896 Plantinga NL, van Asten SAV, Schijffelen MJ, et al . Healthcare professionals challenged by 14 distinct carbapenemase-producing micro-organisms in a war-injured Ukrainian patient. Infection 2023; 53 (4):1517–1521. doi: 10.1007/s15010–025-02523-x. Aro T, Häkkinen TA, Holmberg V, et al . War on AMR: high MDR carriage rates among war-injured Ukrainian refugees. Clin Microbiol Infect . 2025:S1198–743X(25)00350–7. doi: 10.1016/j.cmi.2025.07.010 Joint Trauma System. Infection prevention in combat-related injuries. Joint Trauma System Clinical Practice Guideline No. 24. Fort Sam Houston (TX): Department of Defense, Defense Health Agency; 2021. Joint Trauma System. War wounds: debridement and irrigation. Joint Trauma System Clinical Practice Guideline No. 31. Fort Sam Houston (TX): Department of Defense, Defense Health Agency; 2021.